Phytochemical composition, in vitro antioxidant activity and acute toxicity of Irvingia gabonensis (O’Rorke) baill ethanolic leaf extract - Ewere, Efosa; Uka, Emmanuel; Usunobun, Usunomena (International Journal of Biological Research, 2016)
This study was aimed at determining the phytochemical composition, antioxidant effect and acute toxicity of Irvingia gabonensis (O’Rorke) baill (IG) ethanolic leaf extract. Qualitative phytochemcal analysis was carried out on the ethanolic leaf extract using standard procedures. Different concentrations of the plant extract (20 µg/ml- 100µg/ml) were used to assess its effect on 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical activity, It's reducing power and it total phenolic content. Lorke’s method of acute toxicity was adopted for the acute toxicity study. Results obtained showed the presence of saponins, tannins, flavonoids, cardiac glycosides, steroids, and carbohydrates in the leaf extract. The ethanolic leaf extract of IG significantly (P< 0.05) inhibited the activity of DPPH when compared with the vitamin C standard. IG leaf extract also showed a higher reducing power as compared with the Vitamin C standard. The total phenolic content of IG ethanolic leaf extract was however, significantly (P
Keywords: 1; 1-Diphenyl-2-Picrylhydrazyl (DPPH); Oxidative Stress; Antioxidants; Free Radicals; Irvingia gabonensis (O’Rorke) Baill.